Strategi Kemenangan Ratu-Angga pada Pemilihan Kepala Daerah Sumba Barat Daya Tahun 2024 - Vivin Kurniawaty T. Lunga; Yeftha Y. Sabaat; Philips Y.N. Ndoda (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study aims to analyze the winning strategy of the candidate pair Ratu Wulla and Angga Kaka in the 2024 Regional Head Election (Pilkada) of Sumba Barat Daya Regency. The main focus of this research is how the Ratu-Angga pair gained public support, particularly after Ratu Wulla's controversial decision to resign from her seat in the House of Representatives (DPR RI) to run for Regent. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation.The primary theoretical framework used is Adman Nursal’s 3P political marketing strategy, which includes Push Marketing, Pull Marketing, and Pass Marketing. The findings show that Push Marketing, through face-to-face campaigns and social activities, succeeded in building emotional ties with the community. Pull Marketing effectively utilized social media to reach younger voters. Meanwhile, Pass Marketing was carried out by involving traditional leaders, religious figures, women, and youth who hold strong influence in society. These three strategies were applied synergistically and proved effective in transforming negative public perception of Ratu Wulla resignation into significant political support.The victory of the Ratu-Angga pair, with 49.03% of the valid votes, indicates the success of an inclusive, adaptive, and locally responsive political communication strategy. This research contributes significantly to the understanding of voter behavior dynamics and campaign strategies in the context of local politics in Indonesia.